Building a programme theory of a specialist paediatric palliative and hospice care programme: development process and methodological reflection - Martin Wallner; Daniela Haselmayer; Martin Nagl-Cupal; Jasmin Eppel-Meichlinger; Hanna Mayer (BMC Palliative Care, 2024)
Abstract Background Paediatric palliative and hospice care aims to improve the quality of life of children with life-limiting and life-threatening conditions and their families. The number of these patients has risen significantly in recent years, resulting in an increased need for palliative care for this population. Although the need for paediatric palliative and hospice care is growing, meaningful outcome evaluation to demonstrate its effectiveness as a complex healthcare intervention is in its early stages. For complex interventions (programmes), theory-based evaluations have grown in prominence in recent years. They seek to understand how and why an intervention works by uncovering its underlying mechanisms by means of programme theory. To support both outcome evaluation in paediatric palliative care and a reflective practice of programme theorizing, we aimed to describe the construction of a programme theory for a specialist paediatric palliative and hospice care programme in Austria and to offer a reflective account of its development process. Methods We drew on a combination of theory-based evaluation frameworks to construct a programme theory consisting of an action and a change component. Through multiple iterations, incorporating different stakeholders’ perspectives and drawing on different sources of knowledge and theory, we theorized how and why the programme likely achieves its intended outcomes. Results The programme theory outlines the proposed chains of events, causal mechanisms and outcomes of a specialist paediatric palliative and hospice care programme for children and families in several areas corresponding to its main conceptual tenets. Through a range of activities and interventions, the programme triggers coping and adaptation mechanisms that ultimately contribute to family and child wellbeing in physical, psychological, social, and spiritual dimensions. Established trust and partnership between children/families and healthcare professionals as well as a person-centered and family-centered approach were identified as enabling factors. Conclusions Our findings provide insights into how a specialized paediatric palliative and hospice care programme works to achieve its intended outcomes for children and families. This helps demonstrate its impact, contributing to meaningful outcome evaluation and service improvement.